2021
DOI: 10.1513/annalsats.202006-678oc
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Advance Care Planning for Patients with Hematologic Malignancy: An International Clinician Questionnaire

Abstract: Background: Critical illness is common in hematological malignancy (HM) patients. Advance care planning (ACP) can allow these patients to express their care preferences prior to life-threatening illnesses. The objective of this study was to evaluate physicians' perspectives surrounding ACP in HM patients. Methods:We administered a survey to intensivists and hematologic oncologists who care for patients with HM across Canada and the United Kingdom. Potential respondents were identified from institutions that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 29 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…Patients', their relatives', and HCPs' willingness to communicate about ACP theoretically depends on their beliefs regarding the expected outcomes of that communication (i.e., outcome expectancy beliefs). Three recent studies highlighted negative outcome expectancy beliefs regarding ACP among HCPs [35] and patients with cancer [25,30]. HCPs reported that ACP discussions may overwhelm and upset patients and relatives, inducing unnecessary stress or unleashing uncontrollable emotions, with worrisome psychological outcomes [35].…”
Section: Expectations About Advance Care Planning Discussion Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients', their relatives', and HCPs' willingness to communicate about ACP theoretically depends on their beliefs regarding the expected outcomes of that communication (i.e., outcome expectancy beliefs). Three recent studies highlighted negative outcome expectancy beliefs regarding ACP among HCPs [35] and patients with cancer [25,30]. HCPs reported that ACP discussions may overwhelm and upset patients and relatives, inducing unnecessary stress or unleashing uncontrollable emotions, with worrisome psychological outcomes [35].…”
Section: Expectations About Advance Care Planning Discussion Outcomesmentioning
confidence: 99%
“…Three recent studies highlighted negative outcome expectancy beliefs regarding ACP among HCPs [35] and patients with cancer [25,30]. HCPs reported that ACP discussions may overwhelm and upset patients and relatives, inducing unnecessary stress or unleashing uncontrollable emotions, with worrisome psychological outcomes [35]. Hispanic and Latino patients in the US reported that the wish to safeguard their families from confronting death, and thereby distressing them, was a barrier to engaging in ACP discussions [26 ].…”
Section: Expectations About Advance Care Planning Discussion Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…It also identifies a high-risk cohort in which the risk of ARDS can be discussed together with other risk factors for transplant-related morbidity and mortality at the time of initial consultation. This may also potentially inform advanced care planning discussions ( 13 ). The authors should be commended for putting together one of the largest contemporary cohorts of patients with HCT and describing early factors associated with the subsequent development of ARDS.…”
mentioning
confidence: 99%